Karakteristik dan Perilaku Manajemen Diri pada Penderita Diabetes Mellitus Tipe 2 di Kota Lhokseumawe - Muammar Muammar; Ermi Girsang; Sunarti Sunarti (Jurnal Ragam Pengabdian, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease with an increasing prevalence and has become a major public health concern in Lhokseumawe City. Effective diabetes management depends not only on medical treatment but also on patients' ability to perform self-management. This study aimed to describe the characteristics and self-management behavior of patients with T2DM in Lhokseumawe City. A descriptive analytic study with a cross-sectional design was conducted at primary healthcare centers in Lhokseumawe City in 2026. A total of 64 respondents were selected using purposive sampling. Data were collected using questionnaires on respondents' characteristics and diabetes self-management and analyzed descriptively. The results showed that all respondents were Muslims and belonged to the Acehnese ethnic group. Most respondents had completed senior high school (48.4%) and had a monthly income below IDR 2,700,000 (75.0%). More than half of the respondents (51.6%) had poor self-management, while 48.4% demonstrated good self-management. Poor self-management was associated with educational level, economic status, cultural factors, and limited understanding of and adherence to diabetes management. Socio-cultural characteristics influence self-management behavior among patients with T2DM. Therefore, culturally appropriate health education and family support are needed to improve diabetes self-management and optimize health outcome.